2021
DOI: 10.21608/edj.2021.68553.1557
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint asymmetry in asymptomatic skeletal class I patients

Abstract: Objectives: Analysis of TMJ asymmetry in a sample of asymptomatic skeletal class I patients.Methods : This study was performed on one hundred patients requesting CBCT scans. All patients were skeletal class I pattern. They were all free of TMD symptoms, midline deviation of teeth, open bite, cross bite, congenital craniofacial abnormalities or any systemic diseases which may affect joint morphology such as rheumatoid arthritis. TMJ was evaluated through linear and volumetric analysis. Qualitative condyle posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ahmed ( 13 ) used CBCT scans to measure the correlation of the left and right condyles of subjects without a diagnosis of TMD, thus detecting the asymmetry of the mandible. Toh et al ( 12 ) investigated patients with clinically confirmed TMD and dentofacial deformities, which was contrary to the patients in our research sample.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed ( 13 ) used CBCT scans to measure the correlation of the left and right condyles of subjects without a diagnosis of TMD, thus detecting the asymmetry of the mandible. Toh et al ( 12 ) investigated patients with clinically confirmed TMD and dentofacial deformities, which was contrary to the patients in our research sample.…”
Section: Discussionmentioning
confidence: 99%